Theories of childhood : an introduction to Dewey, Montessori, Erikson, Piaget, and Vygotsky - Mooney, Carol Garhart (Redleaf professional library, 2013)
"Examine the work of five groundbreaking education theorists: John Dewey, Maria Montessori, Erik Erikson, Jean Piaget, and Lev Vygotsky--in relation to early childhood. Theories of Childhood, Second Edition, provides a basic introduction to each theorist and explains the relationship of theory to practice and its impact on real children, teachers, and classrooms"--